COPRODUCTION AND SOCIAL INCLUSION IN PUBLIC SERVICES: A SYSTEMATIC LITERATURE REVIEW - Syafebri, Arrahman; Lionardo, Andries; Putra, Raniasa; Nur Budiyanto, Muhammad; M. Saleh, Hatta (Indonesian Association for Public Administration (IAPA), 2025)
This study examines the relationship between coproduction and social inclusion in public service delivery through a Systematic Literature Review of 36 articles published between 2020 and 2024. The analysis employed thematic and bibliometric techniques using VOSviewer. The findings reveal that coproduction practices tend to be exclusive and have not optimally engaged marginalized groups. Effective inclusion requires deliberative institutional design and the active role of public administrators as facilitators. This study contributes to strengthening a justice-based coproduction model and promotes more participatory and equitable public service reform.